Taxonomic study of the Pagurus forbesii "complex" (Crustacea: Decapoda: Paguridae). Description of Pagurus pseudosculptimanus sp. nov. from Alborán Sea (Southern Spain, Western Mediterranean Sea) - Muñoz, J. Enrique García; Cuesta, Jose A.; Raso, J. Enrique García (Zootaxa, 2014)
Study of hermit crabs from Alboran Sea has allowed recognition of two different morphological forms under what had been understood as Pagurus forbesii. Based on morphological observations with various species of Pagurus, and molecular studies, a new species is described as P. pseudosculptimanus. An overview of species of Pagurus from the eastern Atlantic and Mediterranean Sea is provided.